Ontological-Integrative Islamic Ecotheology: A Comparative Analysis of Badiuzzaman Said Nursi and Achmad Asrori Al-Ishaqi - Moh. Kamil (Civiliza Publishing, 2026)
The contemporary ecological crisis reflects not only environmental degradation but also an ontological and spiritual crisis rooted in the dominance of anthropocentric paradigms that separate humans from their existential relation with nature. In this context, this study aims to reconstruct Islamic ecotheology through an ontological-integrative approach by examining the thought of Badiuzzaman Said Nursi and Achmad Asrori Al-Ishaqi. This research employs a qualitative method with a library research design and a comparative-conceptual approach, using content analysis within an interpretative framework. The findings reveal that Nursi develops a rational-theocentric approach that views nature as divine signs, while Al-Ishaqi, although not explicitly addressing ecological issues, provides a Sufi cosmological and epistemological framework that enables ecotheological reconstruction through the concepts of divine manifestation and the integration of reason and heart. The study concludes that integrating theological rationality and Sufi spirituality produces a transformative model of Islamic ecotheology grounded in ontological awareness and spiritual experience in understanding the human–nature relationship.